PENGARUH EARNING PER SHARE (EPS), RETURN ON EQUITY (ROE) DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PADA PT. INDOFOOD SUKSES MAKMUR TBK PERIODE 2009-2018 - Maryanto Maryanto (Institut Agama Islam Negeri Kerinci, 2022)
One of the objectives of managing finance is to increase shareholder prosperity as measured by the company’s stock price. There are many factors that influence Stock Price, in this study the factors used are Earning Per Share (EPS), Return On Equity (ROE), and Debt to Equity Ratio (DER). In this study the company that was examined was PT. Indofood Sukses Makmur Tbk for the 2009-2018. This study aims to find out partially and simultaneously the influence of Earning Per Share (EPS), Return On Equity (ROE), and Debt to Equity Ratio (DER) on Stock Price in PT. Indofood Sukses Makmur Tbk for the 2009-2018. Researchers use quantitative research methods. The type of data used is secondary data. Data collection techniques, namely with financial statement. With data analysis techniques that use multiple linear regression analysis and hypothesis testing SPSS Version 20.0. The results showed that Earning Per Share (EPS) had a possitive effect and have a significant effect on Stock Prices, Return On Equity (ROE) had a negative effect and did have a significant effect on Stock Price, Debt to Equity Ratio (DER) had a possitive effect and not have a significant effect on Stock Price. Simultaneously Earning Per Share (EPS), Return On Equity (ROE) and Debt to Equity Ratio (DER) affect Stock Price.